Source of output growth in manufacturing industries in Malaysia / Mohamad Ridwan Ratman - Ratman, Mohamad Ridwan (Faculty of Business and Management, 2007)
This study was conducted to examine the source of output growth in manufacturing industries in Malaysia. In this study, it will determine the source of output growth in manufacturing industries such as material input, labour input and capital input that contribute to output growth. This study will analyze each contribution of each source of inputs towards the output growth. The objective of this research is to determine whether there are any relationship between material input, labour input and capital input with the output growth in manufacturing industries. This study use secondary data that have been gathered from Department of Statistics, Malaysia and other relevant sources. Then, the data will be analyzed using Statistical Package for Social Science (SPSS) software that commonly used in analysis. After the data analyzed, it shows that the independent variables (material input, labour input and capital input) have significant relationship with the dependant variable (output growth). Each independent variables show their contribution to the output growth. The results of this study may give some ideas to Malaysia government in the effort to improve the manufacturing industries in Malaysia.